The health impact of an innovative summer camp for older adults: a pilot study using an interdisciplinary collaborative approach - Mei-Hua Yeh; Cheng-Hsien Huang; Yu-Chih Lin; Tung-Jung Huang; Mei-Yen Chen (BMC, 2022)
Abstract Background Healthy aging with dignity and aging in place are important for Taiwanese individuals. Although Taiwan did not experience COVID-19 outbreaks prior to May 2021, many older adults have been encouraged to stay at home since the beginning of the global pandemic in January 2020. Such shelter-in-place recommendations have resulted in significant lifestyle changes, limiting activities associated with aging with dignity such as exercise and community engagement. Few studies have explored how to promote or maintain holistic health practices and physical fitness in older adults residing in rural communities during the COVID-19 pandemic. This pilot study aimed to establish an interdisciplinary collaboration with community care workers (CCWs) and evaluate the impact of an innovative summer camp (ISC) program for older adults residing in rural areas. Methods A quasi-experimental pre-post-test design with an interdisciplinary collaborative approach was implemented. The ISC program was based on a standardized protocol of modified Baduanjin exercise combined with three recreational breathing games. Participants were recruited from three community centers around the western coastal region of Yunlin County between June and August 2020. The ISC program was designed and executed by a nurse-led health promotion research team that collaborated with trained CCWs for 90 min per day, five days per week, for 12 weeks. Participants and CCWs wore facemasks during all activities. Paired t-test was used to measure changes in physical biomarkers, pulmonary lung function, and health-related fitness changes. Results Sixty-eight participants completed the ISC program. The ISC program significantly improved the participants' physiological biomarkers and health-related fitness, including reduced body weight, waistline, and systolic blood pressure, and increased forced vital capacity, biceps arm flexion, and ability to sit and stand from a chair, step with a knee up in situ, and stand on one foot with eyes open. Most participants reported that they felt happy, satisfied, and hoped that this program would be continued in their community center. Conclusions This interdisciplinary, collaborative ISC program improved physical biomarkers and health-related fitness in older adults. Despite limitations, results strongly suggested that primary healthcare providers and CCWs can employ the described ISC program to promote wellness in older adults.